Imobilização de lipase po diferentes técnicas para obtenção de catalizadores estáveis - Santos, Bruna Leal dos [UNESP] (2014)
Lipases, also known as glycerol ester hydrolases , are enzymes that belong to the group of serine hydrolases. The mode of action of lipases is very similar to esterase group, performing the hydrolysis of carboxylic esters of glycerides - forming fatty acids and glycerol. The enzymatic bioconversion processes have been widely used in manufacturing, processing and recovery of raw materials. Advances methodology for immobilization of enzyme have allowed the modification of the kinetic properties and stability of these molecules contributing to the increase in the potential applications of the same. The present work is aimed to study different methods of immobilization of lipases in silica supports, and the effects of this procedure to improve the functionality of enzymes. The immobilization methods chosen for the studies were: physical adsorption, covalent bonding and encapsulation process. The process of immobilization of lipase on Celite (by physical adsorption) was optimized taking into account several parameters such as: pH, the enzyme concentration:support and temperature for enzyme activity. Celite was also used as a support for the immobilization of lipase by covalent bond, where best results were obtained with 20% enzymatic activity at 40 ° C and immobilization efficiency of 50%. The celite was activated with 3-aminopropyltriethoxysilane and glutaraldehyde. Finally, we have studied the possibility of encapsulation of lipase using the precusor tetraethylorthosilicate (TEOS). The results of this last methodology were not satisfactory. These results show that to maintain a good catalytic activity depends on the type of immobilization chose (chemical or physical) and the strength of the interaction between the enzyme and support, which can cause structural distortions in the protein, leading maintenance or a decrease in catalytic activity